Communication Media and the Ensuing Social Activism (Journal of Advanced Research in Journalism & Mass Communication, 2018)
Communication media are crucial to the development of any mass movement (Palmer, 1971). This paper is an attempt to study, quantitatively, the behavioural changes occurring in the millennials belonging to the Union Territory of Pondicherry, caused by the increasing use of WhatsApp and other social media as the sole source of information and a platform for their daily interactions. This paper studies the sociopolitical awareness in the millennials, created by the social media, and the resulting mass mobilization, social aggregation and social activism evidenced in the agitations of #Jallikkattu, #Neduvaasal and Ban Sterlite movement. Adopting Social Cognitive Theory as the conceptual framework, this paper studies the reciprocal determinism in the recent historical events to register dissent. How to cite this article: Krithika KS. Communication Media and the Ensuing Social Activism. J Adv Res Jour Mass Comm 2018; 5(4): 81-87. DOI: https://doi.org/10.24321/2395.3810.201823